Optimalisasi Produksi Alat Gali Muat dan Alat Angkut pada Pengupasan Overburden dengan Menggunakan Metode Antrian dan Kapasitas Produksi di Pit 3 PT. Jambi Prima Coal, Kecamatan Mandiangin, Kabupaten Sarolangun, Provinsi Jambi - Yuyun Frediana; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Jambi Prima Coal is a coal mining company located in Pemusiran Village, Mandiangin District, Sarolangun City, Jambi Province. In the process of production overburden in pit 3, the company uses 1 excavator and 5 dump trucks. In July 2019 overburden production was not achieved. PT. Jambi Prima Coal targets overburden production of 50,000 Bcm / month. However, the actual production of overburden only reached 86.52% of the total production target. This is due to the mismatch of the loading and transportation equipment and the low working efficiency of the mechanical equipment. This study uses the queuing method and production capacity which aims to get the match factor of the loading and transportation equipment in order to achieve the specified target. Based on the results of calculations using the queuing method, it was found that work efficiency increased from 69.5% to 91% resulting in overburden production of 61,669.29 Bcm / month where there was an increase in production by 36.82% and using queuing simulation, the performance of the equipment was matched. MF = 1.01 where the transportation means have experienced no waiting time. By using the production capacity method, the optimal dump truck settings are obtained from 5 units to 4 units.Keywords: Production, Work Efficiency, Overburden, Queue, Production Capacity, Excavator, Dump truckAbstract. PT. Jambi Prima Coal is a coal mining company located in Pemusiran Village, Mandiangin District, Sarolangun City, Jambi Province. In the process of production overburden in pit 3, the company uses 1 excavator and 5 dump trucks. In July 2019 overburden production was not achieved. PT. Jambi Prima Coal targets overburden production of 50,000 Bcm / month. However, the actual production of overburden only reached 86.52% of the total production target. This is due to the mismatch of the loading and transportation equipment and the low working efficiency of the mechanical equipment. This study uses the queuing method and production capacity which aims to get the match factor of the loading and transportation equipment in order to achieve the specified target. Based on the results of calculations using the queuing method, it was found that work efficiency increased from 69.5% to 91% resulting in overburden production of 61,669.29 Bcm / month where there was an increase in production by 36.82% and using queuing simulation, the performance of the equipment was matched. MF = 1.01 where the transportation means have experienced no waiting time. By using the production capacity method, the optimal dump truck settings are obtained from 5 units to 4 units. Keywords: Production, Work Efficiency, Overburden, Queue, Production Capacity, Excavator, Dump truck